Hambatan Tak Terlihat: Rendahnya Literasi Hukum dan Akses Masyarakat terhadap Judicial Review di Indonesia – Analisis Yuridis Normatif untuk Reformasi Inklusif - Anggerina, Desi Puspita; Salatun, Mochamad Ridzky; Siddik, Rifqy Afrizal; Hartono, Toto; Dudikoff, Luthfy Abbad; Muidah, Ida; Candra, Firman Adi (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Judicial review, as a constitutional instrument in Indonesia, aims to uphold the supremacy of the 1945 Constitution (UUD 1945) and protect citizens' constitutional rights. However, low legal literacy and limited public access to this mechanism hinder effective public participation. This article analyzes these issues through a normative juridical approach using secondary data from journals, regulations, and court decisions. The findings indicate that limited understanding, complex procedures, and high costs lead to unequal access, where only influential groups dominate the judicial review of legislation. Recommendations include enhancing legal socialization and procedural reforms to democratize judicial review.